2005
DOI: 10.1890/04-0988
|View full text |Cite
|
Sign up to set email alerts
|

Controls on Nitrogen Cycling in Terrestrial Ecosystems: A Synthetic Analysis of Literature Data

Abstract: Abstract. Isotope pool dilution studies are increasingly reported in the soils and ecology literature as a means of measuring gross rates of nitrogen (N) mineralization, nitrification, and inorganic N assimilation in soils. We assembled data on soil characteristics and gross rates from 100 studies conducted in forest, shrubland, grassland, and agricultural systems to answer the following questions: What factors appear to be the major drivers for production and consumption of inorganic N as measured by isotope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

105
734
16
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 927 publications
(861 citation statements)
references
References 102 publications
105
734
16
6
Order By: Relevance
“…As shown previously, the rates obtained in such a study may not necessarily reflect field rates, which will vary in response to environmental conditions, but rather reflect the potential gross N dynamics after long-term N applications under conditions of the experiment (Arnold et al, 2008). However, the rates of mineralization and nitrification obtained in the current study are within the range reported in other grassland studies (Booth et al, 2005).…”
Section: Application Of a 15 N Tracing Analysissupporting
confidence: 47%
“…As shown previously, the rates obtained in such a study may not necessarily reflect field rates, which will vary in response to environmental conditions, but rather reflect the potential gross N dynamics after long-term N applications under conditions of the experiment (Arnold et al, 2008). However, the rates of mineralization and nitrification obtained in the current study are within the range reported in other grassland studies (Booth et al, 2005).…”
Section: Application Of a 15 N Tracing Analysissupporting
confidence: 47%
“…Denitrification is generally favored by high availability of C and NO 3 − , poor aeration, and neutral pH (Booth et al 2005;Xu et al 2013). In terms of N loss in forest ecosystems, the influence of N deposition and fertilization on denitrification may be insignificant (Gundersen 1991).…”
Section: Denitrification and N 2 O Emissionmentioning
confidence: 99%
“…At the ecosystem level, it may be useful to focus on soil C/N ratios, microbial activities (microbial biomass and respiration), and C availability as the key factors responsible for the effects of N deposition and fertilization on forest soil N mineralization (Aber et al 1998;Booth et al 2005;Corre et al 2007;Tietema 1998;Zhu et al 2013). For instance, data on soil characteristics and gross N transformation rates from across a wide range of ecosystems, forest ecosystems included, show that gross N mineralization rate is positively correlated with microbial biomass and C availability that are negatively correlated with soil C/N ratio (Booth et al 2005).…”
Section: N Mineralizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The depolymerization step, critical in N cycling, is controlled by extracellular enzymes which are often produced by fungi (Jones et al, 2004;Schimel and Bennett, 2004). Ammonium (NH 4 þ ) supplied by N mineralization strongly influences NH 4 þ immobilization (Booth et al, 2005). With high rates of N mineralization and ample NH 4 þ availability, autotrophic nitrification rates in many subtropical/tropical acidic forest soils (soil pH < 5.0) remain low Zhang et al, 2013), indicating that autotrophic nitrification rates in these acidic soils might not be controlled by NH 4 þ availability (Zhao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%